NF‐κB as a regulator of cancer metastasis and therapy response: A focus on epithelial–mesenchymal transition - Mirzaei, Sepideh; Saghari, Sam; Bassiri, Farzaneh; Raesi, Rasoul; Zarrabi, Ali; Hushmandi, Kiavash; Sethi, Gautam; Tergaonkar, Vinay (Journal of cellular physiology, 2022)
Metastasis of tumor cells is a complex challenge and significantly diminishes the overall survival and prognosis of cancer patients. The epithelial‐to‐mesenchymal transition (EMT) is a well‐known mechanism responsible for the invasiveness of tumor cells. A number of molecular pathways can regulate the EMT mechanism in cancer cells and nuclear factor‐kappaB (NF‐κB) is one of them. The nuclear translocation of NF‐κB p65 can induce the transcription of several genes involved in EMT induction. The present review describes NF‐κB and EMT interaction in cancer cells and their association in cancer progression. Due to the oncogenic role NF‐κB signaling, its activation enhances metastasis of tumor cells via EMT induction. This has been confirmed in various cancers including brain, breast, lung and gastric cancers, among others. The ZEB1/2, transforming growth factor‐β, and Slug as inducers of EMT undergo upregulation by NF‐κB to promote metastasis of tumor cells. After EMT induction driven by NF‐κB, a significant decrease occurs in E‐cadherin levels, while N‐cadherin and vimentin levels undergo an increase. The noncoding RNAs can potentially also function as upstream mediators and modulate NF‐κB/EMT axis in cancers. Moreover, NF‐κB/EMT axis is involved in mediating drug resistance in tumor cells. Thus, suppressing NF‐κB/EMT axis can also promote the sensitivity of cancer cells to chemotherapeutic agents. The aim of the present review was to establish that how nuclear factor‐kappaB (NF‐κB) signaling can promote tumor progression via its impact on epithelial‐to‐mesenchymal transition (EMT) mechanism. The NF‐κB/EMT axis was found to be not only involved in increasing metastasis of tumor cells but also can mediate drug resistance and stemness of tumors.